ORGANIZATIONAL PRINCIPLES FOR THE FORMATION OF AN INNOVATIVE MECHANISM FOR MANAGING THE DEVELOPMENT OF AGRICULTURAL ENTERPRISES IN RURAL AREAS - Матієнко, Василь М. (Journal of Strategic Economic Research, 2026)
The article examines the organizational principles of the formation of an innovative management mechanism for the development of agricultural enterprises in rural areas. It is proven that the process of forming an effective management mechanism for the development of agricultural enterprises in rural areas synergistically combines sustainable development, innovation and company strategy, and also includes risk management (provides for the introduction of effective forms of management, the transition to an innovative and sustainable type of development of agricultural enterprises, improving the system of material incentives for employees based on the results of production activities, the formation of a risk assessment system, especially of a military-political nature and their impact on the activities of agricultural enterprises in rural areas). The forecast is analyzed and presented for the implementation of the principles of effective management of the development of agricultural enterprises in rural areas, which clearly demonstrates the growth of the effectiveness and profitability of agricultural enterprises by increasing their competitiveness, introducing innovations and reducing costs for the production of agricultural products, increasing the environmental friendliness of the use of production resources involved in the process of creating agricultural products. All this will generally determine the comprehensive development of rural areas, contributing primarily to the well-being of the rural population.